Jaegu Song’s Borderline Personality Disorder in the Webtoon Girls of the Wild’s - Suzatte Siphra Kezia Tandidatu; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study aims to analyze the classification of Jaegu Song’s borderline personality disorder in the webtoon Girls of the Wild’s. This thesis will use borderline personality disorder theory to analyze Jaegu Song’s behavior and the change in his personality by looking at his actions, dialogues, monologues, and flashbacks. This study analyzes what mental illness Jaegu Song suffered from by finding the symptoms, causes, and effects according to borderline personality disorder theory. It shows that in the webtoon Girls of the Wild’s, Jaegu Song suffered from Borderline Personality Disorder. It can be found that someone might have developed a specific mental illness, even when they appeared to be alright or showed a relatively normal behavior, and sometimes there must be some reasoning on why someone might be seen as problematic or seen as a bad person.